Venezuela 2009: in the midst of difficulties, president Chávez keeps pushing forward his socialist model - López Maya, Margarita; Lander, Luis (Revista de Ciencia Política, 2020)
During 2009 President Chavez´ administration continued with the transformations of Venezuela’s State structures and State-Society relations orientated by the Socialism of the 21st Century Model. In a more intensive way than in prior years sectors of the economy were passed to the State, the recentralization process of the State apparatus kept unfolding and Public Powers continued loosing autonomy to the President of the Republic. This article tackles the complexities of the year through five sections. In the first we describe main features of the Socialism of the 21st Century Model. We do this by revising the official document named Las Líneas Generales del Desarrollo Económico y Social de la Nación 2007-2013, which serves the Government as general policy orientation. Section two presents relevant socioeconomic data of 2009. Section three examines the referendum process that on February 15 resulted in the approval of the Constitutional amendment that allows indefinite elections for the President and all other elected authorities. Section four presents the most important actions taken this year by the National Executive which is today the most important governmental actor. In section five we revise decisions and actions of the rest of the Public Powers to end with conclusions.